Kepemimpinan Visioner Kepala Sekolah - Nur Mukti (Institut Agama Islam Negeri Purwokerto, 2018)
Educational leadership at this time should be based on the identity of the nation that essentially derived from religious and cultural values. This is intended ​​to be able to anticipate changes that occur in the world of education in particular and for the progress achieved outside the school system in general. Visionary leadership emphasizes the importance of vision, which is aimed at realizing effective and competitive organizations. The power of leadership results in various policies and operational work guided by the vision of the organization. An organization that wants to move forward and competitively must have a clear vision and can be understood by all members. A truly visionary leader is required to have a clear goal or vision to be achieved by his organization or himself. If there is no vision, there will be only a person who works without direction and clarity that will be easily shaken and destroyed.